Genetic architecture of innate and adaptive immune cells in pigs - Ballester, Maria; Jové-Juncà, Teodor; Pascual, Afra; López-Serrano, Sergi; Crespo-Piazuelo, Daniel; Hernández-Banqué, Carles; González-Rodríguez, Olga; Ramayo-Caldas, Yuliaxis; Quintanilla, Raquel (Frontiers in Immunology, 2023)
Pig industry is facing new challenges that make necessary to reorient breeding programs to produce more robust and resilient pig populations. The aim of the present work was to study the genetic determinism of lymphocyte subpopulations in the peripheral blood of pigs and identify genomic regions and biomarkers associated to them. For this purpose, we stained peripheral blood mononuclear cells to measure ten immune-cell-related traits including the relative abundance of different populations of lymphocytes, the proportions of CD4+ T cells and CD8+ T cells, and the ratio of CD4+/CD8+ T cells from 391 healthy Duroc piglets aged 8 weeks. Medium to high heritabilities were observed for the ten immune-cell-related traits and significant genetic correlations were obtained between the proportion of some lymphocytes populations. A genome-wide association study pointed out 32 SNPs located at four chromosomal regions on pig chromosomes SSC3, SSC5, SSC8, and SSCX as significantly associated to T-helper cells, memory T-helper cells and γδ T cells. Several genes previously identified in human association studies for the same or related traits were located in the associated regions, and were proposed as candidate genes to explain the variation of T cell populations such as CD4, CD8A, CD8B, KLRC2, RMND5A and VPS24. The transcriptome analysis of whole blood samples from animals with extreme proportions of γδ T, T-helper and memory T-helper cells identified differentially expressed genes (CAPG, TCF7L1, KLRD1 and CD4) located into the associated regions. In addition, differentially expressed genes specific of different T cells subpopulations were identified such as SOX13 and WC1 genes for γδ T cells. Our results enhance the knowledge about the genetic control of lymphocyte traits that could be considered to optimize the induction of immune responses to vaccines against pathogens. Furthermore, they open the possibility of applying effective selection programs for improving immunocompetence in pigs and support the use of the pig as a very reliable human biomedical model.